PENDIDLKAN INKLUSI DI SEKOLAH DASAR SEBAGAI ALTERNATIF PELAYANAN PENDIDLKAN ANAK BERKESULITAN BELAJAR - Djatun, Rachmad (Jurnal Inovasi Pendidikan, 2007)
This research is aimed at knowing the effectiveness of the implementation of inclusion program through the implementation of classroom teacher, visiting teacher, and counseling teacher program in public elementary school. The research was conducted at public elementary schools. The result of the research shows that the most effective model for implementing inclusion program in public elementary school is model 2, that is by implementing counseling teacher program (88.8%), followed by the implementation of visiting teacher program (66.6%) and the least is the implementation of classroom teacher program (33.3%).